Strengthening Service Quality-based Work Culture to Improve Patient Satisfaction: A Case Study at Sayang Regional General Hospital, Cianjur Regency - Neneng Efa Fatimah; Azhar Affandi; Horas Djulius (Al-Hijrah Indonesia, 2025)
Background: Strengthening work culture grounded in service quality is critical for improving patient satisfaction, particularly in public healthcare settings. However, gaps persist in its consistent implementation among health workers and administrative staff. Objective: This study aimed to formulate a strategy for reinforcing a service quality–based work culture to enhance patient satisfaction at Sayang Hospital, Cianjur Regency. Methods: A qualitative case study was conducted using a descriptive-analytical approach. Data were collected through in-depth interviews, participatory observation, and documentation, with source triangulation applied for validation. Informants included hospital management, medical personnel (doctors and nurses), administrative staff, and patients. Data analysis followed the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. Results: The service quality–based work culture at Sayang Hospital remains partial and inconsistently practiced. Patient satisfaction was rated as moderate, with recurring complaints concerning communication, service speed, and staff empathy. Key barriers included a weak quality-oriented performance evaluation system, insufficient training on service excellence, and limited transformational leadership among managers. Conclusion: To strengthen work culture, the study proposes an integrated strategy comprising continuous values-based training and coaching, embedding service quality indicators into performance management, and implementing a balanced reward-and-sanction system to promote patient-centered professionalism.